Historico-theological trajectory of Mary Help of Christians challenges to the life and mission of the archdiocese of Lingayen-Dagupan - Diaz, John Kennedy B. (Mary Help of Christians Theology Seminary : [s.n.], 2020)
This work explores the historico-theological trajectory of Mary, Help of Christians and its challenges to the life and mission of the Archdiocese of Lingayen-Dagupan. The advent of the image of Mary, Help of Christians, and the establishment of the Archdiocese of Lingayen-Dagupan began at the same time in 1928 From that time, Mary, Help of Christians played a significant role to the life and mission of the Archdiocese of Lingayen-Dagupan. The arrival of Mary, Help of Christians, in the Archdiocese of Lingayen-Dagupan led them to build three seminaries and one parish under her tutelage The seminary on the hill of Palapad, San Fabian is the vision fulfilled laid out in 1929 where the Virgen Coronado of the image of Mary, Help of Christians, is enshrined In this view, this thesis-study is a form of the researcher's participation in studying the historical and theological development of Mary, Help of Christians. This thesis-study employs historical and theological analysis. It starts from exploring the history of Mary, Help of Christians based on the Church History. Then, it proceeds with the discussion on the theological foundations of Mary's title as "Help of Christians" utilizing the three traditional sources namely Sacred Scriptures, Sacred Tradition and Magisterial Teachings. From this study, the researcher draws out the challenges from the devotion to Mary, Help of Christians, to the life and mission of the Archdiocese of Lingayen-Dagupan. This thesis- study is also an avenue to recognize and appreciate the devotion to Mary, Help of Christians in the Archdiocese of Lingayen-Dagupan.
Bibliography: pages 177-185.
CHED-La Union
Keywords: Pastoral theology